Dynamic Bitrate Adjustment in Web-based Video Streaming Applications Using HTTP Live Streaming (HLS) - Roh Bintang Jaya, Mabrur; Andriyani, Widyastuti; Kristomo, Domy; Agung Nugroho, Muhammad (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2024)
This research aims to implement Adaptive Bit Rate (ABR) in the web-based video streaming application JBTV using HTTP Live Streaming (HLS). ABR is a technique that enables automatic adjustment of video bitrate according to user network conditions, while HLS is a streaming protocol that supports adaptive streaming based on HTTP. The research methodology encompasses requirements analysis, system design, implementation, and evaluation. During the requirements analysis phase, the identification of JBTV application requirements and the features needed to implement ABR with HLS were conducted. System design involves the selection of suitable ABR algorithms and the architecture design of the JBTV application that supports HLS. Implementation is carried out by developing the JBTV application capable of generating variant streams with various bitrates and performing adaptive playback according to network conditions